Effects of container vegetable gardening on the self-esteem of youth with mild intellectual disability - Bongga, Nenita F. (College of Education, University of the Philippines Diliman, 2013)
This study was conducted to determine whether the self-esteem of youth with mild intellectual disability (MID) could improve after container vegetable gardening. The definition of self-esteem adapted is that of Nathaniel Branden (1969), where it is “the experience of being competent to cope with the basic challenges of life, and of being worthy of happiness." The Rosenberg Self-Esteem Scale (1965) was modified to measure self-esteem of youth with MID and its two components, namely: competence and self-worth. A module with six lessons plans on self-esteem and container vegetable gardening was developed and designed for youth with MID. The results recorded after the end of each module showed that the self-esteem of youth with MID improved, endowing the said respondents with a sense of competence and being persons of worth.